ANALISIS KINERJA KEUANGAN PADA BANK CIMB NIAGA SETELAH DAN SEBELUM MERGER - Pandjaitan, Fransiska Lucyana; Wahyudi, Sugeng (Diponegoro Journal of Management, 2016)
This study aims to analyze the differences in firm performance before and after mergers on CIMB Niaga Bank. Corporate performance is measured by using financial ratio: Current ratio, Acid Test Ratio, Cash Ratio, Return On Asset (ROA), Return On Equity (ROE), Gross Profit Margin (GPM), Net Profit Margin (NPM), Operating Profit Margin (OPM), Total Debts to Equity, Interest Coverage Ratio, Debt Ratio. and Earning Per Share (EPS).Quantitative  method  is  used  in  this  research,  take  the  data  of  CIMB  Niaga  Bank  ‘sfinancial report from OJK (Otoritas Jasa Keuangan) its activity in the period 2004-2013, and analyzed using statistic parametric is used to analyze data. Shapiro Wilk and Sample Pair T test are used to answer hypothesis.The results from this research show that study in 12 financial ratio, Current ratio, AcidTest Ratio, Cash Ratio, ROA, ROE, GPM, NPM, OPM, Total Debts to Equity, Interest CoverageRatio, Debt Ratio. and EPS only Total Debts to Equity show a difference result before and after merger. However, the descriptive statistics changes towards the positive in 7 financial ratios after mergers: Current ratio, ROA, GPM, NPM, OPM, Interest Coverage Ratio, EPS that show the synergy obtained by companies that do mergers